Francis Rudolph Cooke biographical sketch - Cooke, Francis Rudolph, 1848-1911.; Cooke, Paul P.
Biographical sketch pertaining chiefly to Cooke's work as a produce dealer in Center Market, Washington, D.C. Written by Paul P. Cooke.
African American merchant.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: African Americans -- Washington (D.C.); Markets -- Washington (D.C.); Washington (D.C.) -- Commerce; Merchants